THE INFLUENCES OF LOCATION AND PRICE ON CONSUMER PREFERENCES IN TRADITIONAL MARKET (CASE STUDY PASAR BERSEHATI IN MANADO CITY) - Reycel Yudhitia Tarro; Joyce Lapian; Regina Saerang (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2022)
The purpose of this study was to determine how the influences of location and price on consumer preferences in traditional market (Pasar bersehati in Manado city). This study uses quantitative methods with questionnaire data collection techniques. The results of this study indicate that there is a significant influence between location and price on consumer preferences by visitors at Pasar Bersehati Manado. Based on the F test, where Fcount > Ftable (79.107 > 2.70).